Pragmalinguistic analysis of grave threats in Philippine decided cases - GINA M. ORACION (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: This paper aimed to use pragmalinguistic analysis to dissect the language used in death threats. More specifically, this research examined death threats’ syntactic, semantic, and pragmatic aspects in Philippine court decisions.Method: Pragmalinguistic analysis and other forms of qualitative research were used in this investigation. Research for this article was based on Supreme Court rulings in cases involving death threats in the Philippines.Findings: According to the findings, exclamatory sentences are most frequently used when making serious threats, simple sentences are most frequently used when making direct threats, and complex sentences are most commonly used when making conditional threats. Since the speaker commits an act of doing something under a certain condition, threats and challenges can be classified as commissive and directive illocutionary acts.Implications/Novel Contribution: The findings of this study can aid those directly and indirectly involved in the investigation of linguistic crimes, especially those involving death threats.